A Cognitive Occupation-Based Programme for People with Multiple Sclerosis: A Study to Test Feasibility and Clinical Outcomes - Sean Reilly; Sinéad M. Hynes (Hindawi-Wiley, 2018)
Cognitive impairments are common in MS and affect personal, social, and occupational functioning. There is a developing body of evidence highlighting the role of cognitive rehabilitation, but there is still no evidence for a validated holistic approach. The aim of this study was to assess the effectiveness of Cognitive Occupation-Based Programme for People with Multiple Sclerosis (COB-MS) for improving daily life and cognitive impairment. This study used an experimental pretest/posttest design with eight-week follow-up. Participants were recruited from MS networks using convenience sampling. The primary outcome measure was the GAS. Secondary outcomes included the OSA-DLS, CVLT-II, BVMT-R, SDMT, TMT, BRIEF-A, and EMQ-R. Twelve participants were recruited, aged 39-73 years (mean: 55.08; SD: 9.61). There were statistically significant improvements in the GAS (p<.002), CVLT-II: total free recall (p<.000), short delay free recall (p<.018), long delay free recall (p<.008), BVMT-R total recall (p<.000), TMT part B (p<.044), and EMQ-R (p<.006). Except for the BRIEF-A, clinically significant improvements were observed in secondary outcome measures at posttest and follow-up. Limitations include selection bias and subtle practice effects in cognitive measures. Results suggest that a larger scale study is justified considering improvements seen in daily life and cognitive measures.